Integrative supporting techniques for the taxonomy of Schistorchis carneus Lühe, 1906 (Digenea: Megaperidae) with perspective for the existence of species complexes - Mansour, Ali; Karar, Yasser F. M.; Hassan, Hemely Abdel-Shafy; Mohamadain, Hoda S.; Abdel-Hakeem, Sara Salah (Zootaxa, 2025)
The morphology and host-parasite data of Schistorchis carneus Lühe, 1906 indicate low host specificity and geographical range variation, accompanied by a large scale of intraspecific variability and ambiguous molecular phylogeny, confusing in determining biodiversity extent and specificity to a particular host and/or locality. To address the challenging circumstances of records of S. carneus, a detailed morphological description, molecular characterization and species delimitation analyses were conducted using a combination of comparative morphology, molecular phylogeny, multivariate analyses, and host-parasite data. Several morphological features exhibited an extensive intra-variation, as well as a wide morphometric range in many measurements within and across records. Phylogenetic analyses showed that the classification of schistorchiines is highly correlated with the morphology/nature of the oral sucker and highlighted the limitations of ribosomal 28S rDNA and ITS2 rDNA in distinguishing morphologically close/related taxa. Species delimitation analyses reflected the critical importance of host distinction in schistorchiines recognition/differentiation, even those that are indistinct morphologically. The clustering of schistorchiines into certain groups was driven by host differences. Additionally, host variation typically corresponds to a distinct schistorchiine species, even if it is morphologically identical to another. Cluster analysis associated with host-parasite data revealed high morphometric convergence and significant diversity among Egyptian and Sri-Lankan records of S. carneus. It also confirmed the distinction between Indian records from the Bay of Bengal and those from the Gulf of Mannar (previously mentioned as Manaar), each in their own distant group. In conclusion, the records of S. carneus represent a repository for a group of closely related cryptic species. The restricted concept of S. carneus should include only records from the white-spotted puffer, Arothron hispidus (Linnaeus) and the stellate puffer, Arothron stellatus (Anonymous). The Australian specimens from the narrow-lined puffer, Arothron manilensis (Marion de Procé) and the Indian record from the lunartail puffer, Lagocephalus lunaris (Bloch & Schneider) likely represent a free-standing cryptic species with limited distribution, requiring further characterization.